An Introduction to the Local Plants as Source of Essential Oils for The Sepang Village Community, Mempawah Regency, West Kalimantan - Fathul Yusro; Yeni Mariani; Hikma Yanti (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Essential oils are chemical components obtained from plants, are volatile, and give off a distinctive aroma. Essential oils are various products from the perfume industry, soaps, medicines, and cleaning products. Various types of plants produce essential oils. Sepang Village, Mempawah sub-district, West Kalimantan, is one of the villages with the potential for essential oil-producing plants. This community service activity aims to explore the types of essential oil-producing plants planted by the people of Sepang village and increase public knowledge about essential oils and their use. Service activities are carried out through two stages: exploration of essential oil-producing plants and conveying this information to the village community. Based on the exploration results, it was found that the community planted 16 species of plants producing essential oils for cooking spices and medicinal plants. The Sepang village community was very enthusiastic about receiving information, and their knowledge about essential plants and their utilization increased through this activity.